Selenium biofortification enhances ROS scavenge system increasing yield of coffee plants - Mateus, Matheus Pereira de Brito [UNESP]; Tavanti, Renan Francisco Rimoldi [UNESP]; Tavanti, Tauan Rimoldi [UNESP]; Santos, Elcio Ferreira; Jalal, Arshad [UNESP]; Reis, André Rodrigues dos [UNESP] (Elsevier, 2021)
There are conclusive evidences of selenium (Se) deficiency in Brazilian soils and foods. Brazil is the largest producer and consumer of coffee worldwide, which favors agronomic biofortification of its coffee. This study aimed to evaluate effects of foliar application of three formulations and six rates of Se on antioxidant metabolism, agronomic biofortification and yield of coffee beans. Seven Se concentrations (0, 10, 20, 40, 80, 100 and 160 mg L−1) were applied from three formulations of Se (sodium selenate, nano-Se 1500, and nano-Se 5000). Selenium application up to 40 mg L−1 increased the concentration of photosynthetic pigments such as chlorophylls, pheophytins and carotenoids in coffee leaves. Foliar application of Se ranging from 20 to 80 mg L−1 decreased lipid peroxidation and concentration of hydrogen peroxide, but increased superoxide dismutase, ascorbate peroxidase, catalase and glutathione reductase activities in coffee leaves. These results indicated that foliar Se application stimulates antioxidative metabolism to mitigate reactive oxygen species. Foliar application of 20 mg Se L−1 of sodium selenate increased coffee yield by 38%, and 160 mg Se L−1 of nano-Se 5000 increased dramatically coffee yield by 42%. Selenium concentration in grains ranged from 0.116 to 4.47 mg kg−1 (sodium selenate), 4.84 mg kg−1 (nano-Se 1500) and 5.82 mg kg−1 (nano-Se 5000). The results suggest the beneficial effect of Se on the increment of photosynthetic pigments, antioxidative metabolism, increased coffee yield and nutritional quality of grains. The recommended foliar Se application in this study can mitigate abiotic stressors such as high temperatures resulting in higher yield of coffee plants.
Keywords: Antioxidant metabolism; Arabica coffee; Nano-selenium; Sodium selenate